Gendered Language and Identity in South Asian Diasporic Literature: A Comparative Study - Arshad, Faheem; Younas, Vaneeza; Fatima, Areeb (Regional Lens, 2025)
This study explored how gendered language shaped identity in South Asian diasporic literature, focusing on the comparative representation of male and female characters navigating migration, cultural negotiation, and belonging. The research aimed to investigate how linguistic choices, including narrative voice, code-switching, silence, and hybrid expression, reflected and mediated gendered experiences across diasporic contexts. Using qualitative textual analysis, selected novels and short stories were examined to uncover patterns in language that influenced self-representation, familial relations, and social negotiation. The findings revealed that female characters frequently employed reflective and emotionally nuanced language, negotiated silence, and hybrid forms to reconcile cultural inheritance with personal autonomy, whereas male characters more often used declarative and outward-facing speech to assert authority or adaptability. Code-switching and linguistic hybridity emerged as tools for identity negotiation, though the social consequences of language use were distinctly gendered. Generational and familial tensions highlighted the uneven distribution of linguistic authority, with women’s speech subjected to greater scrutiny. The study underscores the role of language as both a constraint and resource in diasporic identity formation, demonstrating that gendered communication practices are central to understanding cultural adaptation, resistance, and self-construction in literary representations of South Asian diaspora.